RANCANGAN MASTERPLAN DESA WISATA LINGSAR DENGAN PENDEKATAN PARIWISATA BERKELANJUTAN - Rini S. Saptaningtyas; Hadiaturrahman, Irfan; Kamil, Muhammad Aulia Alamsyah; Bhujangga, I Gede Andika; Humaida, Maila; Al Amudi, Wafa W.; Finka, Tania; Azizzah, Fatimah Nurul; Marcthini, Mulia; Putra, Ahmad Zamroni (Universitas Mataram, 2025)
Lingsar Tourism Village has significant potential as a cultural and nature-based tourism destination but still faces challenges in sustainable tourism management. This Community Service Program (KKN) aims to design a master plan for a tourism village to enhance its attractiveness and empower the local community. The methods used in this program include field surveys, SWOT analysis, Focus Group Discussions (FGD), site analysis, and tourism design planning. Surveys were conducted to identify the village's potential and issues, while SWOT analysis helped formulate appropriate development strategies. FGD sessions actively involved the community and stakeholders to ensure the plan met local needs. The designs of Alun-Alun, Pura Lingsar, Ricefield Cafe, and Sarasute Bathing Area are the main elements in the development of Lingsar Tourism Village. These designs were created with considerations of sustainability, cultural preservation, and the creative economy to enhance tourism appeal while empowering the local community. Additionally, residents received training in tourism management and MSME (Micro, Small, and Medium Enterprises) development to improve their economic well-being. In conclusion, this program successfully developed a sustainable tourism village master plan for Lingsar, optimizing its cultural and natural tourism potential. The recommendations provided serve as a guide for the local government and community in developing a competitive and sustainable tourism village.